Missed Abortion in a Tertiary Hospital of Eastern Nepal: Efficacy of Sublingual versus Vaginal Misoprostol - Jha, Rani; Rungta, Manoj; Jha, Shailesh Kumar (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Missed abortion is a nonviable intrauterine pregnancy in the presence of a closed cervix and little or no abdominal cramping. WHO recommends Misoprostol as a safe drug in the medical management of missed abortion. This study was conducted to study the efficacy of sublingual versus vaginal misoprostol in the medical management of missed abortion. Methods: A hospital based prospective study was carried out among 212 women with confirmed missed abortion who received 800 μg misoprostol either sublingually or vaginally for the medical management. All women were admitted to hospital for 2 days for observation. If the pregnancy was not completely evacuated in 2 days following misoprostol administration, manual vacuum aspiration or dilatation and curettage was performed for completion. Efficacy was defined as the percentage of women discharged without the need for manual vacuum aspiration or dilatation and curettage. Results: The efficacy of 800 μg misoprostol was high and statistically significant in the sublingual group. Success rate was 80.19% with sublingual route whereas it was only 59.43% with vaginal route (p-value = 0.001).Incidence of complications and side effects like bleeding, abdominal pain, diarrhea and fever was significantly higher in sublingual group. Conclusions: In the medical management of missed abortion sublingual misoprostol achieved a higher rate of complete abortion in comparison to the vaginal route. However, sublingual route showed more adverse effects.